Socioeconomic Determinants of Women’s Choice of Place of Delivery in Cross River State, Nigeria - Etuk Grace Reuben; Armon Margaret Adia Edu (European Scientific Journal, ESJ, 2020)
To increase women’s utilisation ofskilled attendants during pregnancy and childbirth, the government of Cross River State, Nigeria, in 2009, introduced a cost-free maternal health programme. The project was intended to help reduce the high maternal mortality rate in the state, which occurs mainly because of the utilisation of unskilled attendants by women during pregnancy and childbirth. However, the patronage of unskilled attendants by pregnant women in the state has persisted. Thisstudy thus examinesthe factors that influence women’s choices when it comes to where they choose to get care during pregnancy and childbirth. Cross River State, Nigeria, was the study area, and the mixed method was the study design. Women of childbearing age in the state constituted the study population, while a total of 613 respondents were selected purposively to form the subjects for the study. Quantitative data for the study was obtained using a structured questionnaire, while the Focus Group Discussion and interviews were utilised to generate the qualitative data. Two hypotheses were formulated and tested using the ChiSquare and Multiple Regression Analysis as statistical tools. Findings based on the test of the Hypothesis I revealed that delivery demands significantly influence women’s choice of place of delivery. The analysis of the second hypothesis using the multiple regression further revealed that religious belief and income level both had statistically significant p-values of 0.000, which is less than the 0.05 alpha levels of significance; meaning that both religious belief and income level significantly influence women’s choice of place of delivery. Educational status, however, had a p-value (0.078)> 0.05 alpha levels of significance. This is not statistically significant, implying that educational status does not significantly influence women’s choice of place of delivery. The study recommends that beyond making delivery cost-free, the government of Cross River State should adequately equip hospitals to prevent the demands placed on women at the time of birth, which scares a number of them, forcing some to opt for unskilled attendants. Also, the study recommends increased effort towards the empowerment of women to curb the difficulties created by income as well as the intensification of awareness campaigns, among other measures.